How faith-based organizations perceive their role in community development: An exploratory study. Issue 1 (1st January 2021) - Tarpeh, Samson; Hustedde, Ronald
ABSTRACT: This paper examines the research and conceptual literature about the role of faith-based organizations in community development. For the most part, there are relatively few community development studies about faith-based community development groups. This qualitative study explores two research explorations: First, how do Christian faith-based community development organizations in Kentucky perceive and employ the concepts of solidarity and agency (capacity building) in their work. Second, how do they perceive their role in the context of a systems approach to community development as measured through the Community Capitals Framework (CCF) which includes the application of seven capitals in planning and implementation: Natural, cultural, human, social, political, financial and built capitals. While the organizations in our research initiative employ many of these major concepts we learned they do not have an explicit understanding of these approaches. This study also suggests there are also spiritual and emancipatory capitals which merit further investigation as part of a systems approach. The article includes several recommendations about strengthening the potency of faith-based community development organizations through a more explicit understanding of the concepts of solidarity and agency and the community capitals framework and potential partnerships with government and other non-governmental organizations.